Tropical nematology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Plant Parastitic Nematodes In Subtropical and Tropical Agriculture' edited by M Luc, R A Sikora and J Bridge, 1990, 648pp ISBN 0 85198 630 7 price UKL60.00